EFISIENSI PEMASARAN CABAI MERAH KERITING DI KECAMATAN NGEMPLAK KABUPATEN SLEMAN - Istiyanti, Eni (MAPETA, 2010)
The research marketing efficiency of red chili was located in Ngemplak regency Sleman distric purposed to know marketing channel, marketing margin, part of price accepted by farmer each marketing channel and marketing efficiency. The research used descriptive analysis method. About 62 farmer were chosen with cluster method and with sampling ball snow method for got 13 seller. Interview and observation in collecting primary data while the documentation to retrieve secondary data.Result of research indicate that there are three marketing channel in Ngemplak, that is channel I) farmer - retail - consumer, retail there selling red chili Pakem market and Beringharjo market; II channel) farmer - compiler saler - wholesaler - retail - consumer; III channel) farmer - wholesaler - retail - consumer. At I channel, margin marketing that the retailer selling red chili at Beringharjo market larger than Pekem market. While at II channel and III, margin marketing larger ones II channel. At I channel, part of price accepted by farmer from retail selling red chili at Pakem market bigger than Beringharjo market. Economically, I channel which its retail sell red chili to Pakem market more efficient compared to retail selling red chili to Beringharjo market. Technically I channel which its retailer sell red chili to Beringharjo market more efficient compared to retail selling to Pakem market. At II channel and III part of marketing efficiency cannot be determined because final consumer unknown.Keyword : Red Chili, Marketing Channel, Marketing Margin, Part Of Price, Marketing Efficiency